Blood glucose level affects prognosis of patients who received intravenous thrombolysis after acute ischemic stroke? A meta-analysis - Wang, Yue; Jiang, Guannan; Zhang, Jie; Wang, Jingfeng; You, Wanchun; Zhu, Juehua (Frontiers in Endocrinology, 2023)
Background and objectives Intravenous recombinant tissue plasminogen activator (rtPA) thrombolysis is an effective treatment for acute ischemic stroke. Hyperglycemia is a major risk factor for the occurrence, development, and prognosis of ischemic stroke. This meta-analysis purposefully estimates the association between hyperglycemia and poor prognosis in acute ischemic stroke patients receiving intravenous rtPA thrombolytic therapy. Materials and methods According to the predefined inclusion criteria, we searched PubMed, Web of Science, and Cochrane Library databases. The association of high blood glucose(>140mg/dl) with symptomatic intracranial hemorrhage (sICH), poor clinical outcome and mortality at 90 days post-rtPA thrombolysis was studied using both a common effects model and a random effects model. Odds ratios (ORs) were plotted on forest plots. Results Of a total cohort of 2565 patients who received intravenous thrombolytic therapy, 721 had higher blood glucose. High glucose level significantly increased the odds of sICH (OR 1.80; 95% confidence interval(95%CI): 1.30- 2.50) and poor clinical outcome at 90 days (OR 1.82; 95%CI: 1.52-2.19), and all-cause mortality at 90 days (OR 2.51; 95%CI:1.65-3.82). Conclusions In our meta-analysis, high blood glucose was significantly associated with sICH, poor clinical outcome and higher mortality at 90 days.